2011
DOI: 10.1152/physiolgenomics.00226.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to anabolic steroids induces the muscle expression of oxytocin and a more than fiftyfold increase in circulating oxytocin in cattle

Abstract: Chronic exposure to anabolic steroids induces the muscle expression of oxytocin and a more than fiftyfold increase in circulating oxytocin in cattle. Physiol Genomics 43: 467-478, 2011. First published February 15, 2011 doi:10.1152/physiolgenomics.00226.2010.-Molecular mechanisms in skeletal muscle associated with anabolic steroid treatment of cattle are unclear and we aimed to characterize transcriptional changes. Cattle were chronically exposed (68 Ϯ 20 days) to a steroid hormone implant containing 200 mg t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 60 publications
4
46
0
1
Order By: Relevance
“…The same microarray platform and labeling scheme (singlecolor) was used across all experiments, although microarray slide and labeling kit batches as well as lab operators varied. When microarray data using the same platform, but a scanner at a different resolution in a different lab (De Jager et al, 2011) were included, batch correction was much less reliable (data not shown). Therefore, different scanning protocols and inter-laboratory variation might be a limitation for robust meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same microarray platform and labeling scheme (singlecolor) was used across all experiments, although microarray slide and labeling kit batches as well as lab operators varied. When microarray data using the same platform, but a scanner at a different resolution in a different lab (De Jager et al, 2011) were included, batch correction was much less reliable (data not shown). Therefore, different scanning protocols and inter-laboratory variation might be a limitation for robust meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of "omics" technologies (genomics, transcriptomics, proteomics, metabolomics) now offers interesting perspectives to discover reliable and quantifiable markers, which however still await for full implementation in routine analysis. Transcriptome analysis using DNA-microarrays has been recently explored as a screening method to reveal the biological effects of different anabolic compounds and thus support the existing tools to combat the use of these substances in beef cattle (Cannizzo et al, 2013;Carraro et al, 2009;De Jager et al, 2011;Pegolo et al, 2012;Rijk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several authors have shown that exercise, a physiological hypertrophic cue, significantly increases circulating AVP, both in humans and in other mammals, thus posing the theoretical basis for the physiological regulation of muscle hypertrophy by neurohypophyseal hormones [49, 6669]. De Jager et al recently reported that treatment of cattle with anabolic steroids unexpectedly led to a high expression of mRNA encoding oxytocin in muscle, accompanied by a high level of circulating oxytocin in the plasma [70], suggesting that OT is involved in mediating the anabolic effects of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described the effect of 17 β -estradiol (E2) on the gene expression levels in skeletal muscle of veal calves. In particular, De Jager et al (2011) and Divari et al (2013) demonstrated a strong increase in the expression of the oxytocin ( Oxt ) precursor and oxytocin receptor ( Oxtr ) genes in the skeletal muscle of E2-treated veal calves and an intense raise of the plasmatic concentration of circulating oxytocin peptide (OXT). The high serum OXT concentration was likely due to the estrogen influence on OXT production within the supraoptic and paraventricular nuclei of the hypothalamus and/or its release from the posterior pituitary into the blood stream (Chung, McCabe & Pfaff, 1991; Nomura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The high serum OXT concentration was likely due to the estrogen influence on OXT production within the supraoptic and paraventricular nuclei of the hypothalamus and/or its release from the posterior pituitary into the blood stream (Chung, McCabe & Pfaff, 1991; Nomura et al, 2002). Moreover, Oxt precursor gene is increased in bovine skeletal muscle in the late stages of foetal development (De Jager et al, 2011), suggesting that OXT could have a role in muscle growth during both foetal and postnatal development in animals (De Jager et al, 2011; Divari et al, 2013) and that E2 can have a regulatory effect on OXT production in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%